Rabbit dietary supplementation with pale purple coneflower. 1. Effects on the reproductive performance and immune parameters of does. (14th January 2016) - Dabbou, S.; Rotolo, L.; Kovitvadhi, A.; Bergagna, S.; Dezzutto, D.; Barbero, R.; Rubiolo, P.; Schiavone, A.; De Marco, M.; Helal, A. N.; Zoccarato, I.; Gasco, L.
Abstract : Echinacea pallida (EPAL), also known as pale purple coneflower, is a herbaceous flowering plant with immune-enhancement and antioxidative properties. The effect of EPAL on the reproductive performance, serum biochemistry and haematological parameters of rabbit does has been studied here. A total of 100, 21-week-old Grimaud rabbit does, were randomly assigned to two groups. One group was fed a basal diet supplemented with 3 g EPAL/kg diet ( Echinacea group, E), while the other was fed the basal diet without the supplementation (control group, C). The reproductive performance of the does was not affected by the treatment ( P >0.05). The haematological parameters of pregnant rabbits showed that there was no interaction between gestation day and treatment. The EPAL supplementation induced a reduction (−47.3%) in the basophil cell rate (0.55% and 0.29%, for the control and treatment groups, respectively; P =0.049). The gestation day significantly affected most of the haematological parameters ( P <0.05). The white blood cell counts declined progressively after day 14. The mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration, red cell distribution width, mean platelet volume and eosinophils increased steadily throughout the study, and reached a maximum value on day 28. The red blood cells, haemoglobin, haematocrit, mean corpuscular volume and neutrophils increased slightly up to day 14, and then subsequently decreased progressively until day 28. The lymphocytes and platelet distribution width decreased until day 14, and then increased to a maximum value on day 28. No significant effect of gestation day or treatment was observed on the blood serum chemistry. As far as the immune parameters are concerned, no significant differences were observed between groups, while a significant effect of gestation day was observed for lysozymes (6.02 v. 7.99 v. 1.91; for 0, 14 and 28 days, respectively; P =0.014). In conclusion, a lack of effect of EPAL has been observed. In fact, no impacts of EPAL have been observed on the reproductive or haematological parameters of the does. The effects of dietary supplementation with EPAL on the performances, bacterial community, blood parameters and immunity in growing rabbits are reported in the second part of this study.